2009
DOI: 10.1002/mrm.22096
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of T mapping for the evaluation of hip joint cartilage at 1.5T using a three‐dimensional (3D), gradient‐echo (GRE) sequence: A prospective study

Abstract: This study defines the feasibility of utilizing three-dimensional (3D) gradient-echo (GRE) MRI at 1.5T for T* 2 mapping to assess hip joint cartilage degenerative changes using standard morphological MR grading while comparing it to delayed gadolinium-enhanced MRI of cartilage (dGEMRIC). MRI was obtained from 10 asymptomatic young adult volunteers and 33 patients with symptomatic femoroacetabular impingement (FAI). The protocol included T* 2 mapping without gadolinium-enhancement utilizing a 3D-GRE sequence wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 23 publications
(19 reference statements)
5
72
2
1
Order By: Relevance
“…We found a normative mean of 25 ms for the T2* relaxation time in sheep. The corresponding reported values in human beings were 23 to 30 ms [13] and 32 ± 4.5 ms [2]. In contrast to the suggested nonlinear T2* response to cartilage degeneration in human beings [3], we found a very linear correlation with a high correlation coefficient.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…We found a normative mean of 25 ms for the T2* relaxation time in sheep. The corresponding reported values in human beings were 23 to 30 ms [13] and 32 ± 4.5 ms [2]. In contrast to the suggested nonlinear T2* response to cartilage degeneration in human beings [3], we found a very linear correlation with a high correlation coefficient.…”
Section: Discussioncontrasting
confidence: 84%
“…Questions/purposes We asked: (1) Does the histological grading of degenerated cartilage correlate with T2 or T2* values in this ovine FAI model? (2) How accurately can zones of degenerated cartilage be predicted with T2 or T2* MRI in this model? Methods A cam-type FAI was induced in eight Swiss alpine sheep by performing a closing wedge intertrochanteric varus osteotomy.…”
Section: Introductionmentioning
confidence: 99%
“…This effect has been used to assess cartilage composition in healthy volunteers and in patients with hip dysplasia, FAI, and hip osteoarthritis [57,59,60]. T2* mapping is a technique similar to T2 mapping, but T2* mapping has shorter scanning times and is more sensitive to susceptibility artifacts [61]. In the hip, Bittersohl et al [34,61] found a significant correlation between T2* relaxation times and dGEMRIC and histologic assessments of the cartilage, respectively.…”
Section: Compositional Imagingmentioning
confidence: 99%
“…T2* mapping is a technique similar to T2 mapping, but T2* mapping has shorter scanning times and is more sensitive to susceptibility artifacts [61]. In the hip, Bittersohl et al [34,61] found a significant correlation between T2* relaxation times and dGEMRIC and histologic assessments of the cartilage, respectively. Other studies have shown that the T2* values of healthy volunteers significantly differed from those of patients with FAI [62,63].…”
Section: Compositional Imagingmentioning
confidence: 99%
“…Several centers have been or still are working on the development of patient-related outcome measures useful for FAI. Advanced imaging techniques such as dGEMRIC and T2 mapping have become available and have been proposed as prognosticators of outcomes of joint-preserving surgery [1]. Well-designed case-control studies using the mentioned tools should identify which treatments allow reduction of symptoms and deceleration of the development of hip OA.…”
mentioning
confidence: 99%